Electrokinetic Remediation Treatment of Chromium (Cr) Concentration and Distribution in Soil from the PT Semen Baturaja Cement Factory Environment - Alfajrin, Achmad Chalid Afif; Komariah, Rahma Nur; Prasetia, Hendra; Halid, Muhammad Akmal; Aisyara, Arien; Simatupang, Lamtongam; Ghifari, Hamzah Daffa; Widiatama, Angga Jati; Arham, La Ode; Mukti, Aqil Chandra; Ningsih, Dina Widya; Ferdinan, Muhammad Rizky (Diponegoro University Semarang Indonesia, 2025)
PT Semen Baturaja, a cement production company in South Sumatra, Indonesia, holds a Mining Business License of 103.4 hectares, of which 64.23% was reclaimed during 2017–2021. However, the revegetation success rate remains low at only 9%, potentially due to excessive soil chromium (Cr) accumulation. This study investigates the application of electrokinetic remediation to reduce Cr concentrations and improve soil conditions for revegetation. The experiment was conducted on soil samples collected from Disposal Area 4 of PT Semen Baturaja, using a laboratory-scale setup with copper electrodes powered by a 20 V direct current, applied continuously for 48 hours. The results showed that Cr ions tend to migrate toward the anode due to electromigration, while redox reactions influence Cr distribution over time. The highest treatment efficiency was observed in segment one (11.123%), and the lowest in segment three (1.651%). These findings demonstrate the potential of electrokinetic remediation as a viable method for enhancing revegetation in Cr-contaminated post-mining soils.